Pembelajaran Bahasa Arab Menggunakan Metode Mind Mapping Untuk Meningkatkan Pemahaman Kaidah Bahasa Arab Siswa Kelas XII Madrasah Aliyah Roudhatul Muta'allimin II Pulau Panggung Tanggamus - Kasmudi; Ahmad Hadi Setiawan; M. Wisnu Khumaidi; Fajar Saputra; Hadi Purwanto (Al Mufid, 2023)
Arabic is one of compulsory subject in madrasah. This learning emphasizes the students ability to listen, speak,read and write students in Arabic. In learning Arabic, there are many methods that can be applied as a way to provide understanding to students. Among the methods that can be applied in learning Arabic, especially regarding the rules of Arabic ( alqawaid) is the mind mappng method. This learning implementation method is carried out by conveying material in the form of concept maps and providing examples that are easy for them to remember in a structured manner. The material is delivered deductively, which starts by explaining general rules and then continues with the most easily understood examples. Each theme is presented in a concise and structured manner and is interrelated. After this activity was carried out, the students became motivated to continue learning, besides that their ability to understand the rules of the Arabic language was getting better. This can be seen from their enthusiasm during learning and their ability to explain the concepts of Arabic language rules ABSTRAK Bahasa arab merupakan salah satu mata pelajaran wajib yang ada di Madrasah. Pembelajaran ini menekankan pada kemampuan siswa dalam mendengar, berbicara, membaca dan menulis siswa dalam bahasa arab. Dalam pembelajaran bahasa arab, banyak sekali metode yang bisa diterapkan sebagai cara untuk memberikan pemahaman kepada siswa. Diantara metode yang bisa diterapkan dalam pembelajaran bahasa arab khususnya mengenai kaidah bahasa arab ( al-qawaid) yaitu metode mind mapping. Metode pelaksanaan pembelajaran ini dilakukan dengan cara menyampaikan materi dalam bentuk peta konsep dan memberikan contoh-cotoh yang mudah untuk mereka ingat secara terstruktur. Materi disampaikan secara deduktif, yaitu dimulai dengan menjelaskan kaidah umum kemudian dilanjutkan dengan pemberian contoh-contoh yang paling mudah dipahami. Setiap tema disampaikan secara ringkas dan terstruktur serta saling berkaitan.